Rapid development of a decision-aid for people with dementia and their families during COVID-19. (13th April 2021) - West, E.; Kupeli, N.; Moore, K.; Sampson, E.; Aker, N.; Nair, P.; Davies, N.
Abstract : Introduction: COVID-19 as a pandemic has disproportionately affected older adults, including those with dementia. The effects on health and social care systems has necessitated a rapid-response approach to care planning and decision-making in this population, with reflexivity and responsiveness to changing individual and system needs at its core. In light of this, a decision-making tool to help families of persons with dementia was developed using a combination of qualitative data and evidence synthesis. Objectives: To develop a decision-aid using a combination of assessment and evidence-gathering methods for families of persons with dementia. Methods: Semi-structured interviews with helpline staff from national end-of-life and supportive care organisations formed the basis of the tool design. Co-design with people living with dementia, current and former carers and experts in general practice and social care shaped the next stage. Simultaneously, a rapid review of current evidence on making decisions with older people at the end of life was undertaken. Results: Output from interviews covered many topics, including trust, agency and confusion in making decisions in the context of COVID-19. The rapid review of existing evidence highlighted the need to consider both process and outcome elements of decision-making. Conclusions: Combining different sources and forms of evidence was efficient and valuable in creating a novel decision-making tool for persons with dementia and their families within the context of COVID-19. The decision-aid covered care planning, caregiver support systems, access to information and contingency considerations. Upon publication, the tool was adopted by NHS England and other leading healthcare organisations. Disclosure: No significant relationships.